Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

find v(w+3) for v(w)=2w-1

Sagot :

So we have v(w) = 2w - 1

Now we make the following change: w ---> w +3.
So we change every "w" into a "w+3" as follows:

v(w) = 2w - 1 --------> v(w+3) = 2*(w+3) - 1

Let's solve this.
2*(w+3) - 1
2*w + 2*3 - 1
2w + 6 - 1
2w + 5

So

v(w+3) = 2w + 5